Ethics of engineering education - Omar Shuriye, Abdi (IIUM Press, 2009)
Ethics of Engineering Education is a result of an international conference organized by the Faculty of Engineering, International Islamic University Malaysia. It consists of ten parts including teaching technologies, engineering education, engineering professional ethics, engineering and society, research in engineering education and integrating ethics into engineering education. It also covers diverse aspects of engineering education such as outcome-based grading system, engineering career opportunities, engineers’ responsibilities: safety, risk and liability. The book discusses factors that influence ethical perceptions and practices of professional engineers, internet and Islam, ethical requirement in quality software engineering projects, Prophetic philosophy of pharmaceutics, the concept of itqÉn and its role in Muslim life and cultural factors on engineering codes of ethics in Asia, alongside with environmental ethics and global climate change.